Mutilazioni genitali femminili: la lotta dell’Europa contro una silenziosa violenza (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Le pratiche di manipolazioni degli organi genitali femminili - 2. Procedura esercutiva e conseguenze degli atti di alterazione dei caratteri sessuali delle donne - 3. Radici socio-culturali delle pratiche di MGF - 4. Fattore religioso e atti modificativi dei genitali femminili - 5. Le strategie di prevenzione e di contrasto delle MGF nell’Unione europea - 6. Politiche legislative nella lotta contro le MGF - 7. Conclusioni.Denied identities. Female genital mutilation: the fight of Europe against a silent violenceABSTRACT: FGM refers to rituals of manipulation female genitalia and other procedures against female genital organs for non-medical reasons. Usually the practice is carried out on young girls, from childhood to teenagers. These rituals are carried out for cultural, religious and social reasons in the mistaken belief that they will produce a benefit to the girl (to safeguard her virginity, to prepare for marriage, etc.). No religious text prescribes the practice, but is rooted in the culture and beliefs of the communities that practice it. However some religious communities practice the FGM. Rituals do not help the health of the girl subjected, but they can lead to serious health complications or even to death of victim. So FGM is recognised a form of child abuse and a violation of women’s human rights. The EU is committed to eliminating FGM through strategic actions and legislative measures, but mainly changes in attitudes and beliefs among relevant communities are important to ensure FGM is abandoned. It is also important to fight FGM with direct involvement of the religious and political leaders of the communities where the rituals are diffuse. European States are called to cooperate with each other with strategic internal and external actions.